Transcranial magnetic stimulation tracks subminute changes in cortical excitability during propofol anesthesia. Issue 3 (15th February 2020) - Gersner, Roman; Paredes, Carmen; Hameed, Mustafa Q.; Dhamne, Sameer C.; Pascual‐Leone, Alvaro; Rotenberg, Alexander
Abstract: Automated anesthesia systems that continuously monitor cortical excitability (CE) changes to govern drug infusion rates, are desirable. Paired‐pulse transcranial magnetic stimulation (ppTMS), with electromyography (EMG), provides noninvasive CE measures. We tested whether, and with what temporal resolution, ppTMS‐EMG detects dose‐dependent CE in rats anesthetized with continuous intravenous propofol. Motor‐evoked potentials (MEPs) were recorded every 20 seconds as either propofol bolus or change in infusion rate was applied. ppTMS‐derived measures varied in direct proportion to propofol dose with subminute temporal resolution. We conclude that ppTMS‐EMG enables real‐time markers of target engagement by anesthetics that may be incorporated into an automated device.